2022
DOI: 10.1101/2022.03.07.22270699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adequacy of Nasal Self-Swabbing for SARS-CoV-2 Testing in Children

Abstract: BackgroundThe goal of this study was to characterize the ability of school-aged children to self-collect adequate anterior nares (AN) swabs for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing.MethodsFrom July to August 2021, 287 children, age 4-14 years-old, were prospectively enrolled in the Atlanta area. Symptomatic (n=197) and asymptomatic (n=90) children watched a short instructional video before providing a self-collected AN specimen. Health care workers (HCWs) then collected a second… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Moreover, self-collected samples for respiratory viruses have the advantage of earlier collection timed with the onset of symptoms, which may allow better detection 19 . Previous studies have highlighted potential improved uptake, higher satisfaction and reassuring diagnostic accuracy in self and caregiver collected samples 20,21 . In this study, the median age of participants was 6.9 years, and yet 57% of participants inserted the ANS independently, highlighting the potential for self-collection in young children.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, self-collected samples for respiratory viruses have the advantage of earlier collection timed with the onset of symptoms, which may allow better detection 19 . Previous studies have highlighted potential improved uptake, higher satisfaction and reassuring diagnostic accuracy in self and caregiver collected samples 20,21 . In this study, the median age of participants was 6.9 years, and yet 57% of participants inserted the ANS independently, highlighting the potential for self-collection in young children.…”
Section: Discussionmentioning
confidence: 99%
“…There was a correlation between preferences for longer or shorter instructions and the grade level of the intended students, with eight steps suggested for younger students who may need more guidance. Parents and teachers were shown an animated instruction clip and an instructional video developed by researchers at Emory University for their study on children's self-collection [10]. An instructional video featuring children using XpressCollect was identified as more relatable and effective as an instructional tool than an animation.…”
Section: Phases 1 Andmentioning
confidence: 99%
“…Recent studies have demonstrated that adult self-collection and parent sample collection with a nasal swab produces adequate samples for COVID-19 testing that are comparable to clinician collected nasal swab specimens [7][8][9]. Moreover, a recent study conducted by Waggoner et al found that with an instructional video and handout, children ages 4-14 could also self-collect an adequate sample for SARS-CoV-2 detection [10]. However, students' ability to self-collect using nasal swabs in a classroom setting with teacher guidance and the required support materials has not been well established.…”
Section: Introductionmentioning
confidence: 99%